Completude do sistema de informação em tuberculose no Estado do Paraná e sua relação com a região de fronteira - Silva, Marcelle Saldanha (2020)
The study aimed to analyze the completeness of the tuberculosis data in the Sistemas de Informação de Agravos de Notificação (SINAN) and the treatment outcomes in the state of Paraná in the period 2008-2017. Ecological study composed of tuberculosis cases that performed the treatment in Paraná. The data fetched in the SINAN comprise the notification, monitoring and complementary variables. The variables were also grouped as mandatory and essential. Completeness was rated as excellent (<5% incompleteness), good (5 to >10%), fair (10 to<20%), bad (20 to 50%) and very bad (>50%). The global Moran index was used for spatial correlation and the local association index was analyzed. Logistic regression was used to assess the spatial association of variables with the frontier for those that were significant, multiple logistic regression was performed. The study meets resolution 510/2016 of the Conselho Nacional de Saúde. The essential variables had very poor completeness for the antimicrobial sensitivity test, smoking and illicit drugs. There was a worsening in the completeness of the monitoring group over the years, the other groups showed improvement, except in 2014. In the spatial analysis, a “high-high” correlation was noted for schooling, second and sixth month smear microscopy in the Eastern macro-health region and correlation of the “high-high” type in the Northwest macro-region for the second month sputum smear and antimicrobial sensitivity test. No spatial association was found between the variables and outcomes of the cases with the border situation. There was no relationship between the complexity of the variables and the border region, however, there is an indication of the spatial relationship of the second and sixth month bacilloscopy variables, education and antimicrobial sensitivity test. Identifying variables with low completeness can point out weaknesses insertion of data in the system, or failure to follow up on tuberculosis cases. We perceive the need to strengthen the importance of a complete and quality record in health information systems with health professionals, in order to maintain a useful tool in planning and formulation of public health policies and for the evaluation of actions implemented in the fight against tuberculosis.